2022
DOI: 10.3390/electronics12010196
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Wearable Upper-Limb Rehabilitation Assistance Exoskeleton System Driven by Fluidic Muscle Actuators

Abstract: This paper proposed a novel design using a torsion spring mechanism with a single fluidic muscle actuator (FMA) to drive a joint with one degree-of-freedom (DOF) through a steel wire and a proportional pressure regulating valve (PRV). We developed a 4-DOF wearable upper-limb rehabilitation assistance exoskeleton system (WURAES) that is suitable for assisting in the rehabilitation of patients with upper-limb injuries. This system is safe, has a simple mechanism, and exhibits upper-limb motion compliance. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Pneumatic actuators are inherently compliant and have the advantages of low mechanical complexity, weight, and cost for acquisition and maintenance [23,24]. Researchers have already demonstrated functional prototypes of pneumatic medical rehabilitation devices [23,24] as well as pneumatically actuated robots with articulated, i.e., human-like joints [25,26].…”
Section: Am Of Pneumatic Actuatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumatic actuators are inherently compliant and have the advantages of low mechanical complexity, weight, and cost for acquisition and maintenance [23,24]. Researchers have already demonstrated functional prototypes of pneumatic medical rehabilitation devices [23,24] as well as pneumatically actuated robots with articulated, i.e., human-like joints [25,26].…”
Section: Am Of Pneumatic Actuatorsmentioning
confidence: 99%
“…Pneumatic actuators are inherently compliant and have the advantages of low mechanical complexity, weight, and cost for acquisition and maintenance [23,24]. Researchers have already demonstrated functional prototypes of pneumatic medical rehabilitation devices [23,24] as well as pneumatically actuated robots with articulated, i.e., human-like joints [25,26]. Independently of these publications, it has been demonstrated that AM can be used to produce functional prototypes of common pneumatic actuators, such as pneumatic cylinders [27,28] and rotary vane actuators (RVAs) [29].…”
Section: Am Of Pneumatic Actuatorsmentioning
confidence: 99%
“…During physical therapy with doctors, the physiotherapist controls the motion and regulates the interaction joint torque for safe movement with the patient's arms [11]. Similarly, when a robotic manipulator makes contact with the environment (e.g., human) as shown in Figure 1b, controlling both the interaction force/torque and its motion is needed because human-robot interactions can be hazardous if safety is not considered [12,13]. Generally, when a robot interacts with a stiff environment, impedance control is more stable than admittance control, while the reverse applies when the robot interacts with a soft or free-space environment.…”
Section: Introductionmentioning
confidence: 99%
“…IMU sensors were used to control the pressure for the pneumatic actuators. In 2022, Chiou developed a 4-DOF wearable upper limb rehabilitation assistance exoskeleton system (WURAES) that is suitable for assisting in the rehabilitation of patients with upper limb injuries [20]. a proxy-based output feedback sliding mode control (POFSC) was developed to provide appropriate rehabilitation assistance power for the upper limb exoskeleton and to maintain smooth and safe contact between the WURAES and the patient.…”
Section: Introductionmentioning
confidence: 99%